A flexible and stackable 3D interconnect system using growth-engineered carbon nanotube scaffolds. (2nd May 2017) - Jiang, Di; Sun, Shuangxi; Edwards, Michael; Jeppson, Kjell; Wang, Nan; Fu, Yifeng; Liu, Johan
Abstract: One of the critical challenges for realizing flexible electronic systems for a wide range of applications is the development of materials for flexible and stackable interconnects. We propose and demonstrate a three-dimensional (3D) interconnect structure embedded in a polymeric substrate using metal-coated carbon nanotube (CNT) scaffolds. By using two different underlayer materials for the catalyst, one-step synthesis of a dual-height CNT interconnect scaffold was realized. The CNT scaffolds serve as flexible cores for both annular metal through-substrate-vias and for horizontal metal interconnect. The 3D-CNT network was fabricated on a silicon substrate, and once the scaffolds were covered by metal, they were embedded in a polymer serving as a flexible substrate after peel-off from the silicon substrate. The 3D-CNT interconnect network was exposed to mechanical bending and stretching tests while monitoring its electrical properties. Even after 300 cycles no significant increase of resistances was found. Electrically there is a trade-off between flexibility and conductivity due to the surface roughness of the scaffold. However, this is to some extent alleviated by the metalized sidewalls giving the horizontal wires a cross-sectional area larger than indicated by their footprint. For gold wires 200 nm thick, measurements indicated a resistivity of 18 μ Ω cm, a value less than one order of magnitude larger than that of bulk gold, and a value that is expected to improve as technology improves. The mechanical properties of the metalized scaffolds were simulated using a finite element model. The potential scale-up capability of the proposed 3D-CNT network was demonstrated by the stacking of two such polymer-embedded interconnect systems.